Dietary amino acids promote glucagon-like hormone release to generate global calcium waves in adipose tissues in Drosophila - Muhammad Ahmad; Shang Wu; Shengyao Luo; Wenjia Shi; Xuan Guo; Yuansheng Cao; Norbert Perrimon; Li He (Nature Communications)
Abstract Propagation of intercellular calcium waves through tissues has been found to coordinate different multicellular responses. Nevertheless, our understanding of how calcium waves operate remains limited. In this study, we explore the real-time dynamics of intercellular calcium waves in Drosophila adipose tissues. We identify Adipokinetic Hormone (AKH), the fly functional homolog of glucagon, as the key factor driving Ca2+ activities in adipose tissue. We find that AKH, which is released into the hemolymph from the AKH-producing neurosecretory cells, stimulates calcium waves in the larval fat by a previously unrecognized gap-junction-independent mechanism to promote lipolysis. In the adult fat body, however, gap-junction-dependent intercellular calcium waves are triggered by a presumably uniformly diffused AKH. Additionally, we discover that amino acids activate the AKH-producing neurosecretory cells, leading to increased intracellular Ca2+ and AKH secretion. Altogether, we show that dietary amino acids regulate the AKH release from the AKH-producing neurosecretory cells in the brain, which subsequently stimulates gap-junction-independent intercellular calcium waves in adipose tissue, enhancing lipid metabolism.